The significance of clothing imagery in the Pauline Corpus - Kim, Chŏng-hun, 1939- (Journal for the study of the New Testament. Supplement series, 2004)
There are references to clothing throughout PaulGÇÖs letters, and the metaphor constitutes a significant aspect of his theology. The imagery appears several times in his letters: clothing with Christ (Gal 3:27; Rom 13:14), clothing with the new man (Col 3:9GÇô10; Eph 4:22GÇô24), and clothing with the resurrection body (1 Cor 15:49, 50GÇô54; 2Cor 5:1GÇô4). In order to understand the background to this use of the clothing metaphor, Jung Hoon Kim examines similar imagery in the Old Testament, 1 and 2 Enoch, the Apocalypse of Moses, Philo, rabbinic literature, Joseph and Aseneth, the Hymn of the Pe.